Nutritional values of swamp grasses as feed for Pampangan Buffaloes in South Sumatra, Indonesia - Muhakka Muhakka Muhakka; RUJITO AGUS SUWIGNYO; DEDIK BUDIANTA; YAKUP (Society for Indonesian Biodiversity, 2020)
Abstract. Muhakka, Suwignyo RA, Budianta D, Yakup. 2020. Nutritional values of swamp grasses as feed for Pampangan Buffaloes in South Sumatra, Indonesia. Biodiversitas 21: 953-961. This study was aimed at determining the types and quality of vegetation in the swamp area, which could be used as sources of roughage for Pampangan buffaloes in South Sumatra. In this descriptive study, Results showed that the highest crude protein and ether extract contents, 20.56 and 2.92%, respectively, were found in (Neptunia oleracea). The highest ash content of 25.19% was found in Cyperus digitatus. The lowest fiber content (11.01%) was found in Ludwigia hyssopifolia, which also had the lowest content of Neutral Detergent Fiber (NDF) (40.64%). Hemicellulose content was found to be highest (37.14%) in Leersia hexandra. The lowest ADF (23.66%) and lignin (14,84%) contents were found in Nymphaea lotus. N. oleracea was found to have the lowest content (27.08%) of cellulose. It was concluded that the swamp vegetation found in this study consisted of 17 species of grasses and herbs (89.47%) and two species of legumes (10.53%). C. digitatus and L. hyssopifolia were found to have the best nutritional values. Dominant and palatable vegetation with good nutritional values, which were potential to be used as sources of roughage for Pampangan buffaloes, were Hymenachne acutigluma, Oryza rufipogon, Hymenachne amplexicaulis, Polygonum barbatum, and Eleocharis dulcis.